Work and Occupation in French and English Mental Hospitals, c.1918-1939 - Freebody, Jane (Mental Health in Historical Perspective, 2023)
This open access book demonstrates that, while occupation has been used to treat the mentally disordered since the early nineteenth century, approaches to its use have varied across different countries and in different time periods. Comparing how occupation was used in French and English mental institutions between 1918 and 1939, one hundred years after the heyday of moral therapy, the book is an essential read for those researching the history of mental health and medicine more generally. It provides an overview of the legislation, management structures and financial conditions that affected mental institutions in France and England, and contributed to their differing responses to the new theories of occupational therapy emerging from the USA and Germany during the interwar period.